2022
DOI: 10.1155/2022/6517716
|View full text |Cite|
|
Sign up to set email alerts
|

Implementation of a Heart Disease Risk Prediction Model Using Machine Learning

Abstract: Cardiovascular disease prediction aids practitioners in making more accurate health decisions for their patients. Early detection can aid people in making lifestyle changes and, if necessary, ensuring effective medical care. Machine learning (ML) is a plausible option for reducing and understanding heart symptoms of disease. The chi-square statistical test is performed to select specific attributes from the Cleveland heart disease (HD) dataset. Support vector machine (SVM), Gaussian Naive Bayes, logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 26 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…The research reported in [6] also uses statistical models such as SVM, Gaussian Naïve Bayes (GNB), logistic regression, LightGBM, CGBoost, and random forest (RF) to create a classifier that is tested and trained on the Cleveland Clinic Foundation for Heart Disease dataset. The accuracy of the models is measured using performance matrices and confusion matrices.…”
Section: Classical ML Techniquesmentioning
confidence: 99%
“…The research reported in [6] also uses statistical models such as SVM, Gaussian Naïve Bayes (GNB), logistic regression, LightGBM, CGBoost, and random forest (RF) to create a classifier that is tested and trained on the Cleveland Clinic Foundation for Heart Disease dataset. The accuracy of the models is measured using performance matrices and confusion matrices.…”
Section: Classical ML Techniquesmentioning
confidence: 99%
“…Te 10-fold cross validation has been performed and the mean accuracy of 19 MLAs has been listed in Table 3. Ensemble methods [26] such as AdaBoost classifer, Bagging classifer, and extra tree classifer, generalised linear models [27] like logistic regression, passive aggressive classifer, Ridge classifer, stochastic gradient descent classifer, and perceptron, Navies Bayes models [28] like Bernoulli and Gaussian MLA, kNN, and SVM algorithms [29], tree-based methods [30] such as DT classifer and extra tree classifer, and discriminant analysis methods [31] such as linear and quadratic discriminant analysis. Gaussian process MLAs have been evaluated with 10-fold cross-validation.…”
Section: Machine Learning Algorithm (Mla) Selectionmentioning
confidence: 99%
“…Tere are k training and testing iterations. In iteration "i" the test set is partition F i , while the remaining segments, subgroups, or folds are used to train the model collectively [29]. Table 7 and Figure 8 show the 10-fold cross validation accuracy of the three MLAs.…”
Section: Model Performance With Cross-validation (Cv)mentioning
confidence: 99%
“…Compared with conventional methods, this system can avoid human errors and save time. This application shows that enough historical data and precise prediction promotes the survival rate of the patients [4]. Classification methods is one effective way to supervise the machine learning in prediction based on historical data [5].…”
Section: Introductionmentioning
confidence: 97%